Gen Z’s preference for Sharia fraudulent investments: A moral hazard view - Fuadi, Hamdan; Kornitasari, Yenny; Yuana, Pusvita (Jurnal Ekonomi & Keuangan Islam, 2026)
Purpose – This study aims to determine the influence of Islamic financial literacy, profit, religiosity, and affinity variables on Generation Z's preferences in Sharia fraudulent investment practices and to understand whether Generation Z tends to be involved in such practices.Methodology – This research used 200 Generation Z respondents and analyzed them using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method. This method was used to test the relationships among the variables studied.Findings – The results of the analysis show that low Sharia financial literacy has a significant positive effect on Generation Z's preference for fraudulent investment practices. On the other hand, profit, religiosity, and affinity do not have a significant influence on Generation Z's preferences in Sharia fraudulent investment practices.Implications – These findings imply that the low financial literacy of Generation Z can increase their vulnerability to fraudulent investment practices. Therefore, efforts are needed to increase Sharia financial literacy, especially among Generation Z, to reduce the risk of falling into fraudulent investments. In addition, regulators and related parties must increase the supervision of illegal investment practices that take advantage of religious sentiments. Originality – This research makes an original contribution by examining Generation Z's preferences for fraudulent Sharia investment practices, which is a new phenomenon that takes advantage of the high number of Muslims in Indonesia. This research also integrates the variables of Sharia financial literacy, religiosity, and affinity, which have not been widely explored in the context of Sharia fake investment.